2003
DOI: 10.1016/s0735-1097(03)00297-3
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone versus implantable cardioverter-defibrillator:randomized trial in patients with nonischemicdilated cardiomyopathy and asymptomaticnonsustained ventricular tachycardia—AMIOVIRT

Abstract: Mortality and quality of life in patients with NIDCM and NSVT treated with amiodarone or an ICD are not statistically different. There is a trend towards a more beneficial cost profile and improved arrhythmia-free survival with amiodarone therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
161
1
16

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(182 citation statements)
references
References 26 publications
4
161
1
16
Order By: Relevance
“…Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34. One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3. Although anti‐arrhythmic drug therapy has never been clearly shown to reduce SCD in NICM patients experiencing life‐threatening VAs, amiodarone, rather than sodium channel blockers, reduces the occurrence of VAs without the expense of an increase in the mortality in patients with postmyocardial infarction and heart failure 35, 36.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34. One of the randomized trials demonstrated that the mortality and quality of life in NICM patients with a reduced LVEF were similar between those receiving amiodarone, and those with an ICD implantation for nonsustained VT 3. Although anti‐arrhythmic drug therapy has never been clearly shown to reduce SCD in NICM patients experiencing life‐threatening VAs, amiodarone, rather than sodium channel blockers, reduces the occurrence of VAs without the expense of an increase in the mortality in patients with postmyocardial infarction and heart failure 35, 36.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…The clinical manifestation varies, including dyspnea, exertional intolerance, or a consequence of ventricular dysfunction and heart failure. Growing evidence has directed the clinical significance to the prevention of sudden cardiac death (SCD) in NICM patients, which is usually attributed to ventricular tachyarrhythmias arising from a diseased ventricular substrate 2, 3, 4. Therefore, in the risk stratification of NICM patients, given the potential specific therapies and risk prevention strategies for the nonuniform entities of NICM, the identification of the underlying pathogenesis is of clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…First, most of the earlier trials were published during the period of evolving medical therapy; therefore, most of the heart failure patients in different studies were not optimally treated according to the current standards. For instance, the use of beta‐blockers was low in CAT and AMIOVIRT and only DANISH and COMPANION used aldosterone receptor blockers in approximately half of the study population 6, 7, 12, 13. Similarly, angiotensin‐converting enzyme inhibitors/angiotensin receptor blockers were not used uniformly across all the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The six primary prevention trials were the Cardiomyopathy Trial (CAT); the Amiodarone vs Implantable Cardioverter‐Defibrillator Randomized Trial (AMIOVIRT); the Defibrillators in Nonischemic Cardiomyopathy Treatment Evaluation (DEFINITE) Trial; the SCD‐HeFT trial; the Comparison of Medical Therapy, Pacing, and Defibrillation in Heart Failure (COMPANION) Trial; and, more recently, the DANISH trial 5, 6, 7, 12, 13, 14. These trials display noticeable qualitative heterogeneities with regard to study design, comorbidity burden, and follow‐up duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation